Hermeneutika Hadits Fatima Mernissi (Implikasi terhadap Hadis Kepemimpinan Perempuan) - Musdalipa Musdalipa (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2025)
This paper aims to explore the hermeneutics proposed by Fatima Mernissi in reading a hadith, especially those related to the hadith of female leadership. In this case, the hadith narrated by Abu Bakrah's companion stated that "a people who entrust their affairs to women will not be successful." This research is a qualitative research with a descriptive analytical nature, which focuses on analyzing the sanad and matan and revealing how the socio-historical context of a hadith is narrated. The results of this study indicate that the hermeneutic concept proposed by Fatima Mernissi is able to identify bias in the narration of a hadith. In this case, the hadith narrated by Abu Bakra is considered weak for several reasons, such as the incompleteness of Abu Bakra's genealogy, the influence of the social conditions of the hadith, and the lack of credibility of the narrator. Therefore, the hermeneutic approach proposed by Fatima Mernissi provides a reinterpretation of the hadiths so that they are in line with the principle of justice.